Upaya Orang Tua Dalam Mengatasi Perilaku Tantrum Anak Usia Dini - S. Fathiyatul Jannah Jannah; Moh. Syafi’i Idrus (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research will discuss parents efforts in overcoming early-age children's tantrum character in South Pandian Village, Pandian Sumenep. In answering the writing context above the writer uses observation qualitative descriptive method. Exactly, process of writing is to describe and analysis the occurred phenomenon. The main source of this writing is parents in South Pandian Village while the secondary source in this writing is children in South Pandian, Picture, and the documentation. Besides, the way to aggregation data which is used is observation, interview, and documentation. The result of this writing shows that 1) parent effort in overcoming children’s tamper is intended to be calm, give a hug, and shift children's attention. 2) Thread which is faced by a parent to overcome early age children exactly decreasing education from parent in handling children tantrum tamper, decrease to fulfill children demand, the inconsistent parent, the unable parent to give attention to the child and control the emotion, decrease in giving commendation when the child is able to do something.